TINJAUAN YURIDIS ATAS SENGKETA KEPEMILIKAN TANAH DI DESA PEMATANG JOHAR, KECAMATAN LABUAN DELI KABUPATEN DELI SERDANG (STUDI KASUS PUTUSAN PN NO.112/PDT.G/2017/PN.LBP) - Rizal, Said; Chayadi, Bobby; Fredorico, Lineus; Lase, Tania Novebriani (Universitas Ekasakti, 2022)
The importance of soil for human life so it is not surprising if every human being wants to own or control it which results in the emergence of various land problems or land conflicts in Indonesia. Land grabbing cases that have occurred in Indonesia are not something new. The word sequestration itself can be interpreted as: the act of taking rights or property arbitrarily or with not heeding laws and regulations, such as occupying land or houses others, to which they are not entitled. Land grabbing action illegal is an act that is against the law under civil law. The objectives of this study are (1) How to regulate ownership disputes land based on the Civil Code Law, (2) What are the considerations? judges in land ownership disputes in PN No.112/Pdt.G/2017/PN Lbp. Normative juridical research is defined as research law that puts the law as a building system of norms. Sources of data used in this study sourced from primary data and secondary data. This study uses data collection techniques in the form of documentation studies by only analyzing written legal materials. Analysis the data in this study using data analysis research methods qualitative. The results of this study are, Dispute Arrangements Land Ownership Based on the Civil Code, for rights property is arranged in Article 16 of Law No. 5 of 1960 concerning The Basic Agrarian Law concerning hereditary rights, the strongest and most fulfilled and Article 1866 of the Civil Code as well as Article 23 and Article 24 of PP 24/1997 which regulates the proof of land rights for the purposes of registration of land rights. The judge's consideration in deciding that it is true that there has been land grabbing by the Defendant I over the land the inheritance of the plaintiff's parents is due to the evidence of an act, the act is against the law, there is a loss caused by actions taken and it has been proven that there has been a transfer of land rights.